Valuation of Health Inputs and Convenience in New Products - Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2013)
The prevalence of illnesses related to the modern diet and a more sedentary lifestyle has increased markedly over the last few decades. There is therefore a need for effective strategies to promote health and to reduce the prevalence of diet-related diseases. In this paper, we study the willingness to pay for a new concept, healthy canteen takeaways. In the analysis, we depart from a household production model. To control for the endogeneity of the health state, we use a control function approach. The result suggests that health inputs, such as low-fat meat and a larger amount of vegetables, increase respondents' utility. Respondents' valuations of the convenience attribute are very heterogenous, with both positive and negative values. From a policy perspective, the IV estimation turns out to be of importance, with a sign change in the valuation of low-fat meals for individuals with a poor health state (high MBI).
Keywords: C25; D12; D13; I10; 330; endogen; discrete choice; health; household production; instrumental variable